Prevalence of founder mutations in the BRCA1 and BRCA2 genes among unaffected women from the Bahamas. Issue 3 (31st May 2015) - Trottier, M.; Lunn, J.; Butler, R.; Curling, D.; Turnquest, T.; Francis, W.; Halliday, D.; Royer, R.; Zhang, S.; Li, S.; Thompson, I.; Donenberg, T.; et al.
Abstract : Population‐based testing for BRCA1/2 mutations detects a high proportion of carriers not identified by cancer family history‐based testing. We sought to determine whether population‐based testing is an effective approach to genetic testing in the Bahamas, where 23% of women with breast cancer carry one of seven founder mutations in the BRCA1 or BRCA2 gene. We determined the prevalence of founder BRCA mutations in 1847 Bahamian women without a personal history of breast or ovarian cancer, unselected for age or family history. We found that 2.8% (20/705) of unaffected women with a family history of breast/ovarian cancer and 0.09% (1/1089) of unaffected women without a family history carry a BRCA mutation. A total of 38% of unaffected women with a known mutation in the family were found to carry the familial mutation. We previously suggested that all Bahamian women with breast or ovarian cancer be offered genetic testing. These current data suggest that additionally all unaffected Bahamian women with a family history of breast/ovarian cancer should be offered genetic testing for the founder BRCA mutations.